COST OF REMEMBERING: GENDERED EXPERIENCES OF ENGAGING WITH ‘MEMORIES’ ON SOCIAL MEDIA PLATFORMS - Annabell, Taylor (AoIR Selected Papers of Internet Research, 2023)
The use of the term ‘memories’ by social media platforms is not neutral but puts forward a particular understanding of what memories are. I situate the algorithmic resurfacing of the past as ‘memories’ within the dynamic of data colonialism. Memory becomes another layer of human experience that is subjected to datafication and is part of the economic strategy of Facebook to foster increased feelings of intimacy and interdependence. In this paper, I focus on the overlap between the conceptualisations of memory and mnemonic processes by people and commercially driven social media platforms. Drawing on interviews, focus groups and digital traces shared by participants, I examine how gendered subjectivities are being reproduced and intensified by young women as they engage with memories on platforms. First, I address how participants describe their interactions with memory products, focusing on their expectations of typical encounters and entanglements between remembering and feeling. I argue their interpellation into happy remembering by the platform is consequential due to their positionality. Second, I focus on how participants positioned platforms as spaces for preserving and keeping memories beyond the ‘memories’ feature. Third, I look at the role of likes and the quantification of the past within understandings of memories for young women. By exploring intersections of memory, gender and data colonialism, I grapple with how specific groups experience and navigate social media platforms. Navigating gendered pressures and performing normative femininity is part of the cost of engaging with memories for young women.